2004
DOI: 10.1016/j.jacc.2004.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Radial versus femoral approach for percutaneous coronary diagnostic and interventional procedures

Abstract: The radial approach for coronary procedures appears as a safe alternative to femoral access. Moreover, radial access virtually eliminates local vascular complications, thanks to a time-sparing hemostasis technique. However, gaining radial access requires higher technical skills, thus yielding an overall lower success rate. Nonetheless, a clear ongoing trend toward equalization of the two procedures, in terms of procedural success, is evident through the years, probably due to technologic progress of materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
195
2
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 894 publications
(210 citation statements)
references
References 33 publications
7
195
2
6
Order By: Relevance
“…Previous studies showed that the TRA for coronary procedures is a highly safe, effective and comparable technique for both transcatheter diagnostic and therapeutic procedures that yields clinical results similar to transfemoral access (3,5,6,17). Moreover, TRA has several advantages over TFA such as reduced bed rest, shortened hospital length of stay and a reduction in vascular access site complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the TRA for coronary procedures is a highly safe, effective and comparable technique for both transcatheter diagnostic and therapeutic procedures that yields clinical results similar to transfemoral access (3,5,6,17). Moreover, TRA has several advantages over TFA such as reduced bed rest, shortened hospital length of stay and a reduction in vascular access site complications.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized clinical trials and observational studies demonstrated fewer periprocedural complications, shorter length of stay, and better patient satisfaction associated with transradial intervention (TRI) relative to transfemoral intervention (TFI) 1, 2, 3, 4, 5, 6, 7, 8, 9. Based on this evidence, the current US and European guidelines recommend TRI in patients at high risk of bleeding to decrease access site complications 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…It has no nearby important vessels or nerves and due to relatively fixed position of the radial artery, risks of injury to these structures are minimal [17,18]. Also this approach does not need bed rest, allowing for immediate ambulation [1,9,19]. On the other hand, the transradial approach has caused controversies due to its level of success compared to the other method.…”
Section: Discussionmentioning
confidence: 99%
“…However, a transfemoral approach is not possible in all patients, and there are several limitations to this approach. Majority of studies have discussed the advantages of transradial approach since patients find it comfortable and economically advantageous [1][2][3][4][5][6][7]. Today, there is no doubt that a huge number of interventional cardiologists prefer transradial angiography.…”
Section: Introductionmentioning
confidence: 99%